ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM KARAKTER WAYANG PUNAKAWAN - Asrul Anan Siti Juwariyah (Universitas Yudharta Pasuruan, 2017)
Pegajan wayang as learning media is done through storytelling activity. Keep in mind that wayang here is not in physical sense, but in nonphysical form. Teachers simply tell the story of puppet that contains the goodness value and teach the character of the puppet character to be imitated by the students such as the story of Yudhisthira, Pandawa's first sister, who has a wise, responsible, and spirited leader. By wayang intermediate story, students can learn a variety of puppets that deserve to be less worthy of exemplary while fostering knowledge about Indonesian cultural treasuresThe focus of this research is 1) how the puppet character of Punakawan in puppet 2) How to analyze the values of Islamic education in the character of wayang punakawanThis research uses qualitative research with the type of research literature review or often called research library. So in the data collection using primary data sources and secondary data. Technique of data collecting using Dekstop Researh, Documentation Study. As for the analysis technique is done by way of discussion material is based on literature review of the works, either in the form of books or other reading related to this writing.Wayang punakawan consists of semar, gareng, petruk, bagong. While of each character has its own character. Semar has a character in puppetry that is: respected by friends and opponents, semar becomes a respected figure, but still humble, not arrogant, honest and still love sesame. Gareng has a character in the puppet: an unflattering person, what he says is sometimes wrong but he is very funny and ridiculous. Petruk has a character in the puppet: naughty and intelligent, adorable with a smile that dances to the heart, articulate, very funny, likes to quip disbelief with his jokes. Bagong has a character in the puppet: joking when faced with a very serious problem, sassy, like bberish stupid, very funny.